Rotman Lens Based Hybrid Analog–Digital Beamforming in Massive MIMO Systems: Array Architectures, Beam Selection Algorithms and Experiments - Yuan Gao; Khaliel, Maher; Feng Zheng; Kaiser, Thomas (IEEE transactions on vehicular technology, 2017)
Hybrid analog-digital beamforming is a well-known cost-efficient signal processing method for massive MIMO systems. In this paper, we propose a hybrid beamforming massive MIMO system based on Rotman lens analog beamforming with beam selection and digital beamforming. Rotman lens is a low-cost true-time-delay analog beamforming network supporting wide bandwidth signals, which is thus more attractive than the analog beamforming networks based on conventional high-cost phase shifters. To study our system based on Rotman lens, we first examine two potential array architectures, i.e., full-array and subarray architectures, concerning the RF design feasibility, insertion loss, and system scalability. Since the beam selection is required in our system, we propose two beam selection algorithms, i.e., greedy search-based method and branch- and bound-based method, aiming to optimize the hybrid beamforming system in terms of error-rate performance for both the full-array and subarray architectures. To validate our system in practice, the proposed system is also investigated and verified experimentally. In particular, we design and fabricate a sample of Rotman lens operating in the 5-GHz band, whose measured results agrees well with the computer simulation results. The measurement results are incorporated into the Monte-Carlo simulation with the proposed beam selection algorithms to study the error-rate performance. Our simulation results show that the hybrid beamforming system using the low-cost Rotman lens has performance comparable to that of the system using the high-cost phase shifters, and exhibits wideband capability and superior performance over the small-scale MIMO system under the same number of RF transceivers.